Urban Segregation and Metropolitics in Latin America: The Case of Bogotá, Colombia. (5th June 2013) - Thibert, Joel; Osorio, Giselle Andrea
Abstract The patterns of spatial socioeconomic segregation in Latin American cities are changing rapidly as a result of suburbanization and metropolization. However, the political consequences of these urban spatial processes are not well understood. This article uses Orfield's framework of analysis to test the hypothesis that spatial segregation at the metropolitan level is driving political polarization between Latin American cities and their suburbs. With Bogotá as a testing ground, we look for evidence that the mechanisms described by Orfield are at play. We conclude that metropolitan spatial segregation does not drive metropolitan politics in Bogotá and explore some of the theoretical implications thereof.